2014
DOI: 10.1175/jamc-d-14-0032.1
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the Standardized Precipitation Index (SPI) and Its Use to Assess Drought Occurrences in Cameroon over Recent Decades

Abstract: The standardized precipitation index (SPI) is computed and analyzed using 55 years of precipitation data recorded in 24 observation stations in Cameroon along with University of East Anglia Climate Research Unit (CRU) spatialized data. Four statistical distribution functions (gamma, exponential, Weibull, and lognormal) are first fitted to data accumulated for various time scales, and the appropriate functions are selected on the basis of the Anderson–Darling goodness-of-fit statistic. For short time scales (up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 32 publications
2
69
1
1
Order By: Relevance
“…In this study, a 35-year historical record of precipitation data were used to assure the SPI accuracy. For a more detailed explanation of the theory and calculation of SPI, one may refer to these related studies [14,75,76].…”
Section: Standardized Precipitation Index (Spi)mentioning
confidence: 99%
“…In this study, a 35-year historical record of precipitation data were used to assure the SPI accuracy. For a more detailed explanation of the theory and calculation of SPI, one may refer to these related studies [14,75,76].…”
Section: Standardized Precipitation Index (Spi)mentioning
confidence: 99%
“…Associated with global warming and regional precipitation decreases, the potential for increases in drought has been of particular concern in recent years. Many previous studies focused on the development of indices (Byun and Wilhite, 1999;Mu et al, 2013;Tatli, 2015), variabilities (Dai et al, 2004;Kim et al, 2011;Guenang and Kamga, 2014), possible mechanisms associated with atmospheric circulation (Hryciw et al, 2013;Seager and Hoerling, 2014;Zhang and Zhou, 2015) and the impacts (Zhang and Zhou, 2015;Yan et al, 2016) of drought around the world. Drought variation and its impacts have gained much attention in China (Xin et al, 2006;Zhai et al, 2010;Sun and Yang, 2012;Xu et al, 2015;Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CRU precipitation data have already been applied in the area. They were used to compute the multi-scalar Standardized Precipitation Index (SPI), and the results were compared to those from observation data [31]. The results showed that CRU precipitation quite well corroborates the observations.…”
Section: Data Usedmentioning
confidence: 91%